Policing Cinema : Movies and Censorship in Early-Twentieth-Century America - Grieveson, Lee, 1969- (Book collections on Project MUSE., 2004)
White slave films, dramas documenting sex scandals, filmed prize fights featuring the controversial African-American boxer Jack Johnson, D.W. Griffith's The Birth of a Nation--all became objects of public concern after 1906, when the proliferation of nickelodeons brought moving pictures to a broad mass public. Lee Grieveson draws on extensive original research to examine the controversies over these films and over cinema more generally. He situates these contestations in the context of regulatory concerns about populations and governance in an early-twentieth-century America grappling with the.